Rutile-loaded slotted rectangular waveguide array for medical applications - Gupta R.C.; Singh S.P. (My University, 2025)
In this paper, a linear phased array of longitudinal slots in narrow wall of rutile-loaded rectangular waveguide in direct contact with heating medium is theoretically analyzed and reported, which is useful for treatment of cancer in abdomen or chest region. Each slot is excited by a coaxial line probe. It is proposed that the interior of the waveguide be filled with very low loss rutile material to provide a better impedance match to biological tissue. By applying Fresnel-Kirchhoff scalar diffraction field theory, the expression for electric field in heating medium is derived. The contour distribution of Specific Absorption Rate (SAR) in x-z plane and SAR distribution in z-direction due to slotted waveguide array as direct contact applicator is evaluated at 433 MHz. The parameters such as penetration depth, power absorption coefficient and spot size are obtained for slotted waveguide array. The results of slotted waveguide array are compared with those of a single waveguide slot operating at same frequency. It is shown that by changing the phase and amplitude of excitation of each slot of the array, relative amplitude and position of the hot spot can be changed. Results demonstrate that slotted waveguide array offers improvement in SAR distribution and penetration depth. © 2005 IEEE.